Safeguarding motorcyclists: Trialing new PRIME road markings for casualty reduction. (November 2021) - Stedmon, Alex; McKenzie, David; Langham, Martin; McKechnie, Kevin; Perry, Richard; Wilson, Stuart
Highlights: World-first road trial research of PRIME road markings involving 12, 949 motorcyclists. PRIME markings produced significant behaviour changes in speed, position and braking. Supports improved rider behaviour and 'Safe System' approach to casualty reduction. Abstract: Dedicated road markings for motorcyclists were installed on the approach to demanding bends at 10 sites across the West Highlands of Scotland. These road markings were designed as Perceptual Rider Information for Maximising Expertise and Enjoyment (PRIMEs) which presented a series of 'gateway' markings to encourage safer riding. Video data were collected to measure motorcycle speed, position, braking and use of the road markings, before and after the PRIMEs were installed. A total of 12, 949 motorcyclists were observed. Speed reductions were observed across four of the 10 sites, changes in lateral position at the final PRIME gateway marking and apex of the bend were observed across all 10 sites and seven sites respectively; reduced braking was observed at two sites and there was an increase in the use of PRIME road markings across eight of the 10 sites. These findings are discussed in relation to the 'Safe System' approach to improving motorcycle safety.